Studying and Characterization of Coating of Zein-CaSiO3 Composite on Polyetheretherketone Implant Material - Sama Abdulrazzaq; Thekra Ismael Hamad (Hindawi Limited, 2024)
Material-coated implants are placed in the bone and play an essential role in bone regeneration and rapid healing around implants. Polymeric matrix reinforced with ceramic materials is a promising composite material for coating implants. This study aims to determine the effect of mixing various concentrations of zein with CaSiO3 on polyetheretherketone (PEEK) as implant material. The coating was performed using the electrospray method. PEEK disks were used as a control group. The coated disks with different concentrations of zein-CaSiO3 (Group 1: 10% wt, 90% wt), (Group 2: 20% wt, 80% wt), and (Group 3%: 30% wt, 70% wt) were the experimental group. Each group was characterized by atomic force microscopy, field emission scanning electron microscope, Fourier-transform infrared spectroscopy, water contact angle, and adhesion strength. The lowest water contact angle was obtained for Group 1: 10% wt and 90% wt were (26.64° and 27.13°, respectively), and increasing amounts of zein in comparison to quantities of CaSiO3 resulted in increased adhesion strength of the composite material to the substrate. The current study suggested that the higher amount of zein compared to the amount of CaSiO3 mixture coating is achieved by electrospraying, a favorable candidate for coating implants compared to uncoated and coated disks with low concentrations of zein compared to concentrations of CaSiO3.